Narrative Crafting in Tourism Destinations: An Autoethnographic Exploration of Storytelling Techniques for Tour Guides - Ahmad Hudaiby Galih Kusumah; Tomy Andrianto (Politeknik Negeri Bandung, 2023)
This study provides insights into the numerous storytelling techniques tour guides offer to provide visitors with memorable experiences. The study employs an autoethnographic methodology centered on the researchers' extensive background as tourist sector practitioners. The researcher identifies three fundamental tourism storytelling techniques: places, people, and objects. The use of sensory experiences that create a realistic view of a location, strong emotional connections with well-known personalities, the sharing of cultural insights, contrasting and comparing cultures at various locations, highlighting hidden gems, and the use of symbolism or themes to describe a location are all examples of techniques for telling stories about places. Using person-centered storytelling, tour guides can create engrossing narratives by focusing on the character's traits, abilities, and weaknesses, as well as personal tales and journeys. These techniques result in a more authentic and gripping narrative experience. The final approach involves discussing products or physical objects. Guides can narrate the origin and evolution of a product, its cultural significance, future use and potential advancements. This approach provides visitors with a deeper understanding and appreciation of the products unique to the destination. This study contributes to a better understanding of how tour guides can leverage storytelling techniques to enhance visitor experiences and offers practical insights for professional tour guides to improve their narrative delivery.